Environmental disclosures of Malaysian property development companies : towards legitimacy or accountability? - Nik Ahmad, Nik Nazli; Ahmed Haraf, Ahmed Salat (Emerald Group Publishing Limited, 2013)
Purpose – The objective of the present study is to examine the extent, quality, nature and trends of environmental disclosures of Malaysian property development companies for the years 2004, 2005 and 2006. Design/methodology/approach – A content analysis was undertaken of the annual reports of a sample of public listed property development companies in Malaysia for the years 2004, 2005 and 2006. The content analysis examined extent, nature and quality of disclosures, utilising number of sentences for extent and the Clarkson et al. disclosure index for nature and quality. Findings – Malaysian property development companies do not appear to respond to the increased public concern due to recent landslide incidents by increasing the extent or quality of environmental disclosures in their annual reports. Both extent and quality of environmental disclosures are very low and most companies provide mostly ‘‘soft’’ disclosures. They also make very few ‘‘hard’’ disclosures, comprising objective, verifiable data. Thus, the Malaysian Government needs to seriously consider making environmental reporting mandatory and to provide more detailed and comprehensive environmental reporting guidelines. Another major finding is that companies are not consistent in the extent, nature or quality of environmental disclosures made over time. Originality/value – The paper provides empirical evidence of the extent, quality and nature of environmental disclosures in an environmentally-sensitive sector. It is the first study in a developing country to utilise the Clarkson et al. index, which was developed based on the Global Reporting Initiative (GRI) guidelines.